2014
DOI: 10.1111/ced.12346
|View full text |Cite
|
Sign up to set email alerts
|

17β-oestradiol enhances global DNA hypomethylation in CD4-positive T cells from female patients with lupus, through overexpression of oestrogen receptor-α-mediated downregulation of DNMT1

Abstract: 17β-oestradiol enhances global DNA hypomethylation in female SLE CD4+ T cells via downregulation of DNMT1 mediated by ERα overexpression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…One potential mechanism is the epigenetic regulation of ERα in the brain by maternal HFD, which has previously been demonstrated with maternal behaviors and endocrine disruptors 86, 87 . Furthermore, ERα signaling regulates DNA methylation through the control of DNMT genes and other epigenetic factors in a variety of tissues 8890 . The loss of ERα-induced epigenetic modifications along with the modulation of neurogenesis 3133 and neural stem cell proliferation and differentiation 34 during development may abrogate the effects of maternal HFD.…”
Section: Discussionmentioning
confidence: 99%
“…One potential mechanism is the epigenetic regulation of ERα in the brain by maternal HFD, which has previously been demonstrated with maternal behaviors and endocrine disruptors 86, 87 . Furthermore, ERα signaling regulates DNA methylation through the control of DNMT genes and other epigenetic factors in a variety of tissues 8890 . The loss of ERα-induced epigenetic modifications along with the modulation of neurogenesis 3133 and neural stem cell proliferation and differentiation 34 during development may abrogate the effects of maternal HFD.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen downregulates DNA methyl transferase (DNMT) 1 expression and enhances global DNA hypomethylation in CD4 T cells from female SLE patients. While plasma β-estradiol levels were similar between patients and healthy controls, the mRNA expression of ERα but not ERβ was increased in SLE CD4 T cells ( 70 ). Aberrant extracellular regulated kinase (ERK)/MAPK signaling and resultant decrease in DNMT levels leading to DNA hypomethylation of a number of genes has been described and associated with autoimmune disease pathogenesis ( 71 ).…”
Section: Estrogen and T Lymphocytesmentioning
confidence: 99%
“…Wu et al . found that 17β‐oestradiol down‐regulated DNMT1 activity and enhanced global DNA hypomethylation in female SLE CD4 + T cells . In recent years, several studies have indicated that demethylation of inflammatory cytokine genes, such as interleukin (IL)−10, IL‐13, IL‐4 and IL‐6, in CD4 + T cells might participate in the progression of SLE .…”
Section: Dna Methylation Alterations In Lupusmentioning
confidence: 99%
“…Furthermore, killer-cell immunoglobulin-like receptors (KIRs), a family of cell surface proteins expressed on natural killer (NK) cells, and a small portion of T cells, are suppressed primarily by DNA methylation in CD4 1 T cells, enhancing production of IFN-g and macrophage in lupus patients [29,30]. Wu et al found that 17b-oestradiol down-regulated DNMT1 activity and enhanced global DNA hypomethylation in female SLE CD4 1 T cells [31]. In recent years, several studies have indicated that demethylation of inflammatory cytokine genes, such as interleukin (IL)210, IL-13, IL-4 and IL-6, in CD4 1 T cells might participate in the progression of SLE [32,33].…”
Section: Abnormal Dna Methylation In Lupus T Cellsmentioning
confidence: 99%